Harmonizing variant classification for return of results in the All of Us Research Program. Issue 8 (28th December 2021) - Harrison, Steven M.; Austin‐Tse, Christina A.; Kim, Serra; Lebo, Matthew; Leon, Annette; Murdock, David; Radhakrishnan, Aparna; Shirts, Brian H.; Steeves, Marcie; Venner, Eric; Gibbs, Richard A.; Jarvik, Gail P.; et al.
Abstract: The All of Us Research Program (AoURP) is a historic effort to accelerate research and improve healthcare by generating and collating data from one million people in the United States. Participants will have the option to receive results from their genome analysis, including actionable findings in 59 gene‐disorder pairs for which disorder‐associated variants are recommended for return by the American College of Medical Genetics and Genomics. To ensure consistent reporting across the AoURP, in a prelaunch study the four participating clinical laboratories shared all variant classifications in the 59 genes of interest from their internal databases. Of the 11, 813 unique variants classified by at least two of the four laboratories, classifications were concordant with regard to reportability for 99.1% (11, 711), with only 0.9% (102) having reportability differences. Through variant reassessment, data sharing, and discussion of rationale, participating laboratories resolved all 102 reportable differences. These approaches will be maintained during routine AoU reporting to ensure continuous classification harmonization and consistent reporting within AoURP.